Efficient clustering scheme for OFDMA-based multicast wireless systems using grouping genetic algorithm - Tan, Chee Keong; Chuah, Teong Chee; Tan, Su Wei; Sim, M. L. (Institution of Engineering and Technology (IET), 2012)
The spectral inefficiency problem faced by the conventional multicast schemes in OFDMA-based multicast systems is investigated. To improve spectral efficiency, the multicast problem is formulated as a combinatorial clustering optimisation problem where multicast groups are divided into smaller subgroups and subcarriers are allocated to each subgroup. A novel multicast clustering scheme based on a grouping genetic algorithm is proposed to maximise the aggregate data rate. Simulation results show that the proposed scheme can achieve near-optimal performance while outperforming the conventional unicast and multicast schemes.